Experimental and Numerical Study of Failure Behavior and Energy Mechanics of Rock-Like Materials Containing Multiple Joints - Ri-hong Cao; Hang Lin (Advances in Materials Science and Engineering)
This paper investigates the influence of joint geometry parameters on the characteristic stress, failure pattern, and energy mechanism of multiple jointed rock-like specimens under uniaxial compression. Both the laboratory and numerical results show that the higher value of UCS occurs when α is around 0° and γ changes from 15° to 30° or when α is around 30° and γ changes from 45° to 75°. However, the lowest value appears when α is around 45° and γ changes from 15° to 30°. The CDiS (critical dilatancy stress) and CIS (crack initiation stress) show a similar tendency to UCS. Moreover, the specimens present different failure modes for various levels of α, γ, and k, and the failure mode can be classified into four categories: stepped path failure; failure through parallel plane; failure through cross plane; material failure. In addition, with higher strength, the input energy and strain energy are higher than those with lower strength. Dissipation energy is affected by the failure modes of the specimens. At the same time, when k changes from 0.2 to 0.6, the boundary energy, strain energy, and dissipation energy show a decreasing trend.